The mitigation effectiveness of farmers’ adaptation measures for seasonal drought: evidence from major rice growing areas in southern China - Zhu, Kangrui; Xu, Wen; Chen, Boou (Frontiers in Environmental Science, 2023)
To assess the mitigation effectiveness of farmers' adaptation measures for seasonal drought, we focused on the 2013 seasonal drought disaster in Jiangxi Province, southern China, the major rice growing areas, a typical case from China. First, we surveyed 755 farm households in Jiangxi Province that were harmed by seasonal drought in 2013. Based on the data from this survey, we constructed econometric models and used an instrumental variable approach to evaluate the effects of adaptation measures on the rice yield reduction due to seasonal drought, and then examined the factors influencing the capacity of farmers to adopt effective adaptation measures. The results show that: (1) More adaptation measures adopted by farmers can be effective in reducing the negative impacts of seasonal droughts on rice production. (2) All three types of measures, structural adjustment adaptation measures (SAAM), irrigation adaptation measures (IAM) and engineering adaptation measures (EAM) can significantly mitigate rice yield reduction due to seasonal drought, and SAAM and IAM perform more effectively. (3) Farmers' social communication, frequency of droughts and access to disaster prevention information can help to increase the capacity of farmers to adopt adaptation measures, while distance from roads has a negative effect. (4) In terms of the different supportive policies, policies with higher-level agents and human support are more effective in increasing the ability of farmers to adopt adaptation measures. Our findings provide the following policy insights. On the one hand, it is necessary to increase the capacity of farmers to adopt measures by improving their social communication, incentivizing them to access information on resilience, and providing more supportive policies, especially policies with higher-level agents and human support. On the other hand, farmers should be encouraged to actively adopt adaptation measures to reduce the hazards of seasonal drought, especially SAAM and IAM.